Restorative Justice in Criminal Law Reform in Indonesia - Vience Ratna Multi Wijaya; Ermania - Widjajanti (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
Restorative justice is indispensable in preventing an increase in crime. As countries in the world such as Canada, the United Kingdom and even the United Nations' 1975 Fifth Annual Session began to discuss Restorative Justice, it was expected that member states would also begin to use it in their positive laws. Restorative justice can monetize the level of capacity in the Penitentiary, reduce budget costs for the criminal justice process. Restorative justice in Indonesia began to exist in SE Kapolri, Kajari and SE MA. The main issue in this paper is "How to regulate Restorative Justice in Indonesian Criminal Law Reform  ?". This article uses a legal research method based on law and ease approach by using normative approach, which aims to solve the problem about mentions. The target reached by implementing restorative justice. Generally, this article expectedly may contribute in the development of criminal justice system as an effort to embody fairness and certainty, justice and benefits.